Nitrogen nutrition of tomato plant alters leafminer dietary intake dynamics. (May 2017) - Coqueret, Victoire; Le Bot, Jacques; Larbat, Romain; Desneux, Nicolas; Robin, Christophe; Adamowicz, Stéphane
Graphical abstract: Highlights: T. absoluta larvae improved C, N and water status of mined tomato leaves. An original method evaluated miner's resource ingestion and frass production. N limitation forced larvae to ingest less N and water, but more C and biomass. Under N limitation, larvae produced more frass. Under N limitation, time needed for larvae to reach pupae was delayed. Abstract: The leafminer Tuta absoluta (Meyrick) is a major pest of the tomato crop and its development rate is known to decline when nitrogen availability for crop growth is limited. Because N limitation reduces plant primary metabolism but enhances secondary metabolism, one can infer that the slow larval development arises from lower leaf nutritive value and/or higher plant defence. As an attempt to study the first alternative, we examined the tomato- T. absoluta interaction in terms of resource supply by leaves and intake by larvae. Tomato plants were raised under controlled conditions on N-sufficient vs. N-limited complete nutrient solutions. Plants were kept healthy or artificially inoculated with larvae for seven days. Serial harvests were taken and the N, C, dry mass and water contents were determined in roots, stems and leaves. Leaf and mine areas were also measured and the N, C, dry mass and water surface densities were calculated in order to characterize the diet of the larvae. The infestation of a specific leaf lessened its local biomass by 8–26%, but this effect was undetectable at the whole plant scale. Infestation markedly increased resource density per unit leaf area (water, dry mass, C and N) suggesting that the insect induced changes in leaf composition. Nitrogen limitation lessened whole plant growth (by 50%) and infested leaflet growth (by 32–44%). It produced opposite effects on specific resource density per unit area, increasing that of dry mass and C while decreasing water and N. These changes were ineffective on insect mining activity, but slowed down larval development. Under N limitation, T. absoluta consumed less water and N but more dry mass and C. The resulting consequences were a 50–70% increase of C:N stoichiometry in their diet and the doubling of faeces excretion. The observed limitation of larval development is therefore consistent with a trophic explanation caused by low N and/or water intakes.